Non-linear Differential Equations and Rotating Disc Electrodes: Padé approximationTechnique. (20th July 2017) - Chitra Devi, M.; Rajendran, L.; Yousaf, Ammar Bin; Fernandez, C.
Abstract: Rotating disc electrodes are preferred devices to analyze electrochemical reactions in electrochemical cellsand various rotating machinery such as fans, turbines, and centrifugal pumps. This model contains system of fully coupled and highly non-linear equations. This manuscript outlines the steady state solution of rotating disc flow coupled through the fluid viscosity, to the mass-concentration field of chemical species and heat transfer of power-law fluid over rotating disk. Furthermore, a simple analytical expression (Padé approximation) of velocity component/ self-similar velocity profiles is derived from the short and long distance expression. Our analytical results for all distance are compared with previous small and long distance and numerical solutions (Runge-Kutta method), which are in satisfactory agreement.